Implementasi Strategi Pembelajaran Kontekstual dalam Meningkatkan Sikap Sosial Siswa IPS di SMA Negeri Simpang Hulu: Implementation of Contextual Learning Strategies in Improving Social Attitudes of Social Studies Students at Simpang Hulu State Senior High School - Sumardi Sumardi; Pitalis Mawardi Baging (ITScience (Information Technology and Science), 2026)
21st-century education demands learning that is not only oriented towards cognitive aspects but also capable of developing students' social attitudes. Social studies learning plays an important role in fostering cooperation, empathy, and social responsibility, but school practices remain teacher-centered, resulting in suboptimal development. This condition demands the application of contextual learning strategies that link material to students' real lives. This study aims to describe and analyze the implementation of contextual learning strategies to improve students' social attitudes in social studies at Simpang Hulu State Senior High School. The study used a descriptive qualitative approach. The research subjects were social studies teachers and 10th-grade students, selected purposively. Data were collected through observation, interviews, and documentation, then analyzed using an interactive model through data reduction, data presentation, and conclusion drawing. The results showed that contextual learning strategies have been implemented through the components of constructivism, learning communities, and questioning, although not optimally and still partially. Learning that links material to real contexts encourages students' social interactions through group discussions. Students' social attitudes improve in cooperation and responsibility, while empathy develops gradually. Supporting factors include curriculum flexibility, environmental potential, and students' social interactions. Inhibiting factors include teacher preparedness, student learning habits, time constraints, and learning media. This strategy plays a crucial role when implemented consistently and systematically.